2011
DOI: 10.1016/j.piutam.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of fatigue-initiated subacromial impingement: clarifying mechanisms

Abstract: Subacromial impingement in the shoulder precedes many cases of rotator cuff pathology. However, debate exists regarding the mechanism, and even existence, of fatigue-initiated impingement. The controversy centers on two primary impingement mechanisms: 1) superior humeral head migration and 2) scapular reorientation. A linked series of in vivo experiments and in silica simulations accomplishes the integration of stochastic, orthopedic, geometric, kinematic, physiologic, literature-derived, and experimental data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…Narrowing of the subacromial space is believed the beginning stage in rotator cuff pathologies that eventually result in tendon tearing. 48,49 However, Michener et al reported a minimal detectable change of 0.8 mm and Leong et al a minimal detectable change of 2.1 mm for AHD. 50,51 Assuming similar method in the sonography measurement of AHD as Michener et al, the AHD changes following fatigue would not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Narrowing of the subacromial space is believed the beginning stage in rotator cuff pathologies that eventually result in tendon tearing. 48,49 However, Michener et al reported a minimal detectable change of 0.8 mm and Leong et al a minimal detectable change of 2.1 mm for AHD. 50,51 Assuming similar method in the sonography measurement of AHD as Michener et al, the AHD changes following fatigue would not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even small AHD changes may be very important. 48 Decreasing the subacromial space may result in shoulder impingement syndrome and compress the tissues occupied the space. Biceps tendon, subacromial bursa and of particular concern the supraspinatus tendon are within this space.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while research suggests that subacromial space integrity can be maintained even in the presence of muscle fatigue through scapular reorientation, an important consideration reported by several researchers is the considerable inter-subject variability that exists both in controlled and fatigued conditions. 61 This implies that the risk of SAIS is non-uniform across the population. As described, the subacromial tissues, notably the supraspinatus tendon, are highly susceptible to injury in seemingly benign healthy scenarios (i.e.…”
Section: Fatigue-induced Kinematic Trendsmentioning
confidence: 99%